The Perceived Effectiveness of Supervision In Cognitive Behavioral Therapy Training - Erkan Kuru; Kadir Ozdel; S.Olga Guriz; Yasir Safak; Ilker Ozdemir; M.Hakan Turkcapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Psychotherapy is a general name for the problem solving techniques to address mental disorders or struggles through verbal interaction. Cognitive Behavioral Therapy (CBT) is one of the leading approaches in psychotherapy field. The first aim of this study; to evaluate the contribution of theoretical and supervision trainings perceived by mental health professionals to their CBT skills and personal development. The second one was to evaluate the CBT training process in psychotherapy training. To this end, 54 mental health professionals who agree to participate the study were given questionnaires each consisting of 18 items. This questionnaire was created by three supervisors who have been certified by the Academy of Cognitive Therapy (ACT). Mean duration of work as a mental health professional were 7.6 years. Mean duration of using psychotherapy in their clinical practice were 4,8 years. Mean duration of application of CBT as a psychotherapy modality were 3,2 years. Mean durations of theoretical and supervision trainings the participants had participated were 55,4 hours and 69,1 respectively. Seventy-nine point six of the participants reported that the theoretical training had contributed to their CBT practice at quite to too much levels. Fifty-nine point two of the participants reported that the same training contributed to their personal development at quiet to too much levels. For the supervision traning these perceived contributions were 92,6 % and 70,4% respectively. That the therapists reported high degree of satisfaction with the theoretical and supervision trainings they need to accomplish is promising about the psychotherapy training in Turkey. Besides, results of this study suggests that although theoretical training is of perceived value, supervision has been perceived as had given extra contribution. [JCBPR 2016; 5(3.000): 119-124]